Digitalization and Digital Capabilities in Business Performance: A Bibliometric Analysis - Taib, Azuraidah; Nasir, Noor Emilina Mohamed; Awang, Yunita (Advances in Social Sciences Research Journal, 2024)
This study aims to identify and analyze academic literature on the topic of digitalization and digital capabilities in business performance. For this purpose, a bibliometric analysis is performed to identify the main topics, authors, sources, most cited articles and nations in the literature. Based on search results for keywords related to business, management, and accounting, a total of 271 documents were found with a total of 6315 citations. The bibliometric analysis shows the progress of the scientific literature on the topic of the study and highlights the topics used by most authors that could be studied by future researchers. However, the study is subject to limitations as certain articles may not be identified due to the specifics of various subtopics and sub-topics within the research